PROGRAM EVALUATION - STRENGTHENING CHARACTER EDUCATION IN INTEGRATED ISLAMIC JUNIOR SECONDARY SCHOOL - Siti SAHRONI; Abdul Madjid LATIEF (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2019)
This article aims to evaluate the success of Strengthening Character Education Program implemented in Integrated Islamic Junior Secondary School at Depok. The descriptive qualitative evaluation was used throughout the study. Using naturalistic approach, the evaluator collected the data through observation, in-depth interviews and relevant document study. Interviews were conducted with the foundation chief, principals, vice principals, teachers, parents, and students. This research concludes that the implementation of the Program run as expected. During implementation, the principal was assisted by his vice principal and teachers in planning, organizing, supervising, and controlling the curricula, student activities, and infrastructures. The implementation results in improved student character as intended by the objective of the program. It is expected that this endeavor can be maintained with better and improved facilities.